Write the equation that satisfies the parameters: two times the sum of a number and 24 equals the difference of 76 and that same number . (1 point) 2(x + 24) = x - 76; 2(x + 24) = 76 - x; 2x + 24 = 76 - x; 2x + 24 = x - 76

1 answer

To create an equation based on the given parameters, we should first understand the statement:

"Two times the sum of a number and 24 equals the difference of 76 and that same number."

Let's break this down:

  1. Let \( x \) represent the unknown number.
  2. The sum of the number and 24 is \( x + 24 \).
  3. Two times that sum is \( 2(x + 24) \).
  4. The difference of 76 and that same number is \( 76 - x \).

Now, we can set up the equation based on the statement:

\[ 2(x + 24) = 76 - x \]

This indicates that the correct equation from the provided options is:

2(x + 24) = 76 - x.